2020
DOI: 10.1590/2236-8906-104/2019
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of Pyrostegia venusta (Ker Gawl.) Miers seeds

Abstract: Seeds of Pyrostegia venusta (Ker Gawl.) Miers) were desiccated at 25 °C on silica gel for 0 h (T0), 7 h (T1) and 24 h (T2), reaching moisture contents of 6.5%, 4.4% and 3.8%, respectively. Seeds were frozen rapidly in liquid nitrogen (+LN) at -263 °C.min.-1 and after 72 h, they were thawed slowly at room temperature (25 ± 2 °C) at a speed of 5 °C.min.-1. Seed germinability evaluation before (-LN) and after freezing (+LN) was conducted at 25 °C, on paper roll substrate, and germinated at 16 hrs light/8 hrs dark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The imbibition curve showed that the germination started early for seeds exposed to LN. According to Salomão, Santos, and José (2020), exposure to LN can be used as a treatment to overcome dormancy in species with impermeable integument, and the immersion of seeds of some species into LN causes the formation of cracks in the integument, usually due to the pressure on them, which makes the seeds less rigid, facilitating the imbibition process and leading to an improvement in the germination process.…”
Section: Resultsmentioning
confidence: 99%
“…The imbibition curve showed that the germination started early for seeds exposed to LN. According to Salomão, Santos, and José (2020), exposure to LN can be used as a treatment to overcome dormancy in species with impermeable integument, and the immersion of seeds of some species into LN causes the formation of cracks in the integument, usually due to the pressure on them, which makes the seeds less rigid, facilitating the imbibition process and leading to an improvement in the germination process.…”
Section: Resultsmentioning
confidence: 99%
“…The importance of water content is reported in several studies and for various plant materials, such as seeds of Punica granatum L. (Punicaceae) (Silva et al 2015), seeds of Encholirium spectabile Martius ex Schultes f. (Bromeliaceae) (Ferrari et al 2016), seeds of Pyrostegia venusta (Ker Gawl.) Miers (Salomão et al 2020), as well as seeds, pollen, protocorms, structures similar to protocorms, apexes extracted from in vitro plants and meristematic tissues of orchids (Popova et al 2016).…”
Section: Discussionmentioning
confidence: 99%